Every Face Has a Name - Gertten, Magnus (Sweden, 2015)
On April 28, 1945, hundreds of survivors of Nazi concentration camps arrive in the harbour of Malmö, Sweden. As they disembark, Swedish news photographers film them. Now, 70 years later the survivors are watching this archive footage for the very first time and as they discover themselves they re-experience the emotions from this special day. Bernard Kempler was 9 years old when he came to Malmö. He survived the war by dressing up as a girl. Elsie Ragusin from New York City was visiting her grandparents in Italy when she was accused of being a spy. She was put in a boxcar and sent to Auschwitz. These and many other emotional stories are evoked for the first time in Every Face Has a Name and the archive reveals an extraordinary blend of stories coming from Jewish survivors, Norwegian resistance men, Polish mothers with new-born babies and British spies. All united in the moment of freedom. Moments and scenes also taking place all over the world today. Endless streams of war survivors arriving to a new country. All anonymous. Faces without names.
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films